PELATIHAN PEMANFAATAN PLATFORM MERDEKA MENGAJAR (PMM) DALAM IMPLEMENTASI KURIKULUM MERDEKA BAGI GURU MIPA - Handayani, Dewi; Amir, Hermansyah; Candra, I Nyoman; Alperi, Muzanip (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2024)
Observations carried out at SMAN 2 Rejang Lebong show that readiness to implement the independent curriculum and the use of the Platform Merdeka Mengajar (PMM) in its implementation is still lacking. So, it is necessary to assist in the use of PMM in implementing the independent curriculum at SMAN 2 Rejang Lebong. The aim of this service is to introduce the features in PMM for Mathematics and Science (MIPA) teachers at SMAN 2 Rejang Lebong. Providing knowledge and skills for MIPA teachers at SMAN 2 Rejang Lebong regarding the use of PMM in implementing the independent curriculum. The target of this activity is MIPA teachers at SMAN 2 Rejang Lebong. The total number of targets is around 22 people. Furthermore, participants who had received training directed teachers in other fields of study who had not been invited to this activity. The methods used in this activity are training and workshops, guided assignment work and evaluation monitoring at the final stage. Based on the results of the service that has been carried out, teachers are very enthusiastic about participating in the training. As many as 100% of teachers have successfully opened an account at PMM and 85% have utilized the features available at PMM.